1996
DOI: 10.1002/(sici)1097-0118(199605)22:1<15::aid-jgt3>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The average Steiner distance of a graph

Abstract: The average distance μ(G) of a graph G is the average among the distances between all pairs of vertices in G. For n ≥ 2, the average Steiner n‐distance μn(G) of a connected graph G is the average Steiner distance over all sets of n vertices in G. It is shown that for a connected weighted graph G, μn(G) ≤ μk(G) + μn+1−k(G) where 2 ≤ k ≤ n − 1. The range for the average Steiner n‐distance of a connected graph G in terms of n and |V(G)| is established. Moreover, for a tree T and integer k, 2 ≤ k ≤ n − 1, it is sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
49
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 0 publications
1
49
0
Order By: Relevance
“…It was observed by Plesník [29] that among all trees of given order the star minmimises the Wiener index. It was shown by Dankelmann, Oellermann and Swart [6], and by Li, Mao and Gutman [21] that the same statement holds also for the Steiner k-Wiener index. Plesník [29] also showed that among all trees of order n and diameter d, the Wiener index is minimised by the tree obtained from a path on d + 1 vertices by attaching n − d − 1 vertices to a centre vertex of the path.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…It was observed by Plesník [29] that among all trees of given order the star minmimises the Wiener index. It was shown by Dankelmann, Oellermann and Swart [6], and by Li, Mao and Gutman [21] that the same statement holds also for the Steiner k-Wiener index. Plesník [29] also showed that among all trees of order n and diameter d, the Wiener index is minimised by the tree obtained from a path on d + 1 vertices by attaching n − d − 1 vertices to a centre vertex of the path.…”
Section: Introductionmentioning
confidence: 61%
“…with equality if and only if G is a path. Dankelmann, Oellermann and Swart [6] and Li, Mao, Gutman [21] showed that this result extends to the Steiner k-Wiener index.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The average Steiner distance µ k (G) of a graph G, introduced by Dankelmann, Oellermann and Swart in [12], is defined as the average of the Steiner distances of all k-subsets of V (G), i.e. For more details on average Steiner distance, we refer to [12,13].…”
mentioning
confidence: 99%
“…In fact, no such algorithm is even known for other classes of graphs such as the partial 2-trees, Halin graphs, interval graphs, or distance hereditary graphs for which the Steiner problem has an efficient solution. The ideas presented in [1] initiated the study of the average Steiner n-distance of a graph (see [5]).…”
mentioning
confidence: 99%